(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the threefold properties of speech sounds articulatory, acoustic, and perceptual—providing a comprehensive overview of how speech sounds are produced, transmitted, and interpreted. The articulatory properties focus on how speech sounds are formed through the manipulation of the vocal tract, distinguishing between consonants and vowels based on their production mechanisms. The acoustic properties examine the physical characteristics of sound waves, such as frequency, amplitude, and formants, which shape the transmission of sound through the air. The perceptual properties delve into how humans hear and process speech, emphasizing pitch, loudness, and timbre, and highlighting the role of cognitive mechanisms in interpreting sounds in context. The article emphasizes the interconnection between these properties and their significance for understanding human language, with applications in linguistics, speech technology, and cognitive science. By studying the intricate relationship between articulation, acoustics, and perception, the article contributes to a deeper understanding of speech as a dynamic and complex process in human communication.